1985
DOI: 10.1143/jjap.24.356
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition of Lipid Multilamellar Aqueous Suspension under High Pressure I. Investigation of Phase Diagram of Dipalmitoyl Phosphatidylcholine Bimembrane by High Pressure-DTA and -Dilatometry

Abstract: The pressure and temperature phase diagrams of DPPC bilayers have been obtained by DTA and dilatometry. Under atmospheric pressure DPPC shows three phase transitions at 42°C, 36°C and around 18°C, corresponding to the main-, pre- and sub-transitions respectively. Throughout our experiments we discovered very interesting phenomena in these transitions due to the effect of pressure and are as follows. First, the presence of a tricritical point on the pre-transition line has been found at about 2.5 kbar and 78°C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…The pressure dependence of the melting transition has been investigated before by various authors. 12,13,16,[18][19][20][21]36,37 It has been shown that the shift of the lipid melting transition is linear with the applied hydrostatic pressure in a pressure range up to at least 2 kbar. However, these authors were mainly interested in the shift of the transition point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure dependence of the melting transition has been investigated before by various authors. 12,13,16,[18][19][20][21]36,37 It has been shown that the shift of the lipid melting transition is linear with the applied hydrostatic pressure in a pressure range up to at least 2 kbar. However, these authors were mainly interested in the shift of the transition point.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2) is comparable to previous studies for the transition temperature. The value for the proportionality factor, γ, averaged over various literature values yields a mean value γ j ) 7.34‚10 -4 mL/J for DMPC MLV, 12,14,16,20,21 γ j ) 7.07‚10 -4 mL/J for DPPC MLV, 14,16,[19][20][21]39,40 and γ j ) 7.63‚10 -4 mL/J for distearoyl phosphatidylcholine MLV. 13,20 Similar numbers where found for dieladioyl phoshatidylcholine and palmitoyl oleoyl phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the L ␤ I phase is also induced by an application of pressure. It was found that bilayers of CnPCs, such as dimyristoyl-PC (DMPC: C14PC) and dipalmitoyl-PC (DPPC: C16PC), form the fully L ␤ I phase under high pressure [10][11][12][13][14][15][16][17][18]. In the L ␤ I phase, hydrocarbon chains of the CnPC molecules in one of the monolayers constituting a bilayer extend beyond the region of the bilayer midplane and alternately interpenetrate into the other opposing monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid bilayer membranes of diacylphosphatidylcholines (diacylPCs), of which two identical saturated fatty-acid chains are bound to the glycerol backbone by ester linkage, have been thoroughly examined by several physico-chemical techniques [1][2][3][4][5][6][7][8][9]. Such bilayer membranes form various kinds of phases depending upon experimental conditions, and the characteristic gel-phase polymorphism is observed.…”
Section: Introductionmentioning
confidence: 99%